@Katolistikorg Manfaat konten Instagram sebagai sarana dakwah - azis prasanto; Julia puspita dewi (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2024)
Instagram @katolicitasorg offers a variety of content related to the Catholic faith. This research uses Instagram content @katolicitasorg as a news tool in the digital era. This research was conducted to determine the benefits of Instagram @katolicitasorg content for Catholic Religious Education students at Sanata Dharma University, Yogyakarta. This study uses a qualitative method. Data was collected through observation, interviews, FGD and questionnaires. The data obtained were confirmed using triangulation techniques. Based on the results of this research, the majority of students felt that Instagram content @katolicitasorg had positive benefits because it provided a new and clear understanding of the reasons for praying for the dead according to the Catholic Church. Students feel that the topics presented are relevant to their experiences. They become stronger and motivated to pray for their deceased relatives and friends. Most students stated that this content was superior in its delivery because it used various sources combined into several slides and was enhanced with visual perspectives in the form of images. However, several students were open and suggested that the @katolicitasorgi Instagram content needed changes to the reporting model, such as videos, language adaptations (such as direct quotes) and also the addition of sources from the New Testament.